Republic of Belarus : Selected Issues. (IMF Staff Country Reports; Country Report, 2010)
The global financial crisis that erupted in late 2008 had a profound impact on Belarus's economy. The unprecedented external shock necessitated a strong set of corrective measures, including exchange rate adjustment. This Selected Issues paper analyzes whether the corrective measures in the exchange area are sufficient to restore current account sustainability. It examines various pieces of evidence, including basic indicators of competitiveness as well as the macroeconomic balance and external sustainability approaches. It concludes that the substantial misalignment observed in the end of 2008 has been largely corrected.